2018
DOI: 10.3390/app8050718
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Comb-Based WDM Transmission Systems Enabling Joint Signal Processing

Abstract: We review the use of optical frequency combs in wavelength-division multiplexed (WDM) fiber optic communication systems. In particular, we focus on the unique possibilities that are opened up by the stability of the comb-line spacing and the phase coherence between the lines. We give an overview of different techniques for the generation of optical frequency combs and review their use in WDM systems. We discuss the benefits of the stable line spacing of frequency combs for creating densely-packed optical super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 109 publications
0
35
0
1
Order By: Relevance
“…The recovered CW signal then seeded an electro-optic comb generator [107]. In these type of transceivers, the phase-locked nature of the optical carriers are exploited in the DSP for the DWDM signals, showing reduced DSP complexity [5]. OIL is crucial in these systems as it regenerates CW tones with high OSNR.…”
Section: B Optical Local Oscillator Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…The recovered CW signal then seeded an electro-optic comb generator [107]. In these type of transceivers, the phase-locked nature of the optical carriers are exploited in the DSP for the DWDM signals, showing reduced DSP complexity [5]. OIL is crucial in these systems as it regenerates CW tones with high OSNR.…”
Section: B Optical Local Oscillator Recoverymentioning
confidence: 99%
“…Laser synchronization plays important roles in numerous applications. In optical communications, synchronized lasers are used as local oscillators (LOs) to reduce the complexity and latency in coherent receivers [2]- [5]. In conjunction with optical frequency comb, OIL coherently demultiplexes optical tones for dense wavelength division multiplexed (DWDM) systems or super channel transmitters [6]- [9], enabling high spectral efficiency communications.…”
Section: Introductionmentioning
confidence: 99%
“…Having access to multiple channels impaired by the same phase noise means that the phase estimation can be made more efficient in terms of phase tracking capabilities [15][16][17], or power consumption of the digital electronics [18]. It has been suggested that joint phase processing can be implemented with optical frequency comb sources [19][20][21][22] but a proof in a transmission experiment is still outstanding. In the receiver, one even and one odd channel can be picked to be received simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…To alleviate this drawback, we investigate the possibility of sharing the laser source over multiple channels. Recent research has illustrated that a frequency comb is a viable alternative as a source for multiple wavelength-division multiplexing (WDM) channels [17]. When expanding our test setup with an optical waveshaper acting as a band pass filter, we could narrow down the spectrum of the frequency comb to less than 2.5 nm without any observable penalty.…”
Section: Fig 2: Circuit Layout and Die Micrographmentioning
confidence: 99%